2017
DOI: 10.1021/acs.jmedchem.6b01745
|View full text |Cite
|
Sign up to set email alerts
|

Total Syntheses and Biological Activities of Vinylamycin Analogues

Abstract: Natural depsipeptide vinylamycin was reported to be an antibiotic previously. Herein we report vinylamycin to be active against K562 leukemia cells (IC = 4.86 μM) and be unstable in plasma (t = 0.54 h). A total of 24 vinylamycin analogues with modification of the OH group and chiral centers were generated via a combinatorial approach. The lead compound 1a was subsequently characterized as having the following: no antimicrobial activity, significantly higher plasma stability (t = 14.3 h), improved activity agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…From the results of an MTT assay, BE‐43547A 2 was the most effective at inhibiting the growth of Panc‐1 cells compared to the other derivatives. Xenograft zebrafish model experiments using Panc‐1 cells further demonstrated that BE‐43547A 2 shows higher anti‐pancreatic cancer activity than the compounds 2 , 2 a , and TBDPS‐ ent ‐vinylamycin (Figures S4 and S5). The significantly reduced inhibitory activities of 1 c , 2 , 2 a , and 2 b imply that both a double bond at C8−C9 and an S configuration at C15 are essential to maintain inhibitory activity against Panc‐1 cells.…”
Section: Methodsmentioning
confidence: 94%
“…From the results of an MTT assay, BE‐43547A 2 was the most effective at inhibiting the growth of Panc‐1 cells compared to the other derivatives. Xenograft zebrafish model experiments using Panc‐1 cells further demonstrated that BE‐43547A 2 shows higher anti‐pancreatic cancer activity than the compounds 2 , 2 a , and TBDPS‐ ent ‐vinylamycin (Figures S4 and S5). The significantly reduced inhibitory activities of 1 c , 2 , 2 a , and 2 b imply that both a double bond at C8−C9 and an S configuration at C15 are essential to maintain inhibitory activity against Panc‐1 cells.…”
Section: Methodsmentioning
confidence: 94%
“…Treatment of engrafted leukemic blasts from patient 4 reflected the poor response during the treatment coarse. Zebrafish have received more attention during the last decade as an embryonic model host for xenografts, with nine publications exploring engraftment of other leukemic blast cell types to date [21,24,25,36,[38][39][40][41]. The ALL-ZeFiX assay both provides proof-of-principle for BCP-ALL exgraftment and extends the clinical utility of drug testing in immunosuppressed zebrafish avatars with quantifiable endpoint analysis and a 5-day assay format.…”
Section: Discussionmentioning
confidence: 99%
“…From the results of an MTT assay,B E-43547A 2 was the most effective at inhibiting the growth of Panc-1 cells compared to the other derivatives. Xenograft zebrafish model experiments using Panc-1 cells further demonstrated that BE-43547A 2 shows higher antipancreatic cancer activity than the compounds 2, 2a,a nd TBDPS-ent-vinylamycin [14] (Figures S4 and S5). Thes ignificantly reduced inhibitory activities of 1c, 2, 2a,and 2b imply that both ad ouble bond at C8 À C9 and an S configuration at C15 are essential to maintain inhibitory activity against Panc-1c ells.…”
Section: Zuschriftenmentioning
confidence: 93%